2023
DOI: 10.48550/arxiv.2301.12109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The TIME Table: Rotation and Ages of Cool Exoplanet Host Stars

Abstract: Age is a stellar parameter that is both fundamental and difficult to determine. Among middleaged M dwarfs, the most prolific hosts of close-in and detectable exoplanets, gyrochronology is the most promising method to assign ages, but requires calibration by rotation-temperature sequences (gyrochrones) in clusters of known ages. We curated a catalog of 249 late Kand M-type (𝑇 eff =3200-4200K) exoplanet host stars with established rotation periods, and applied empirical, temperature-dependent rotation-age relat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 146 publications
0
1
0
Order By: Relevance
“…Empirically calibrated relations between age and period can be used to estimate the ages of individual field stars. Gaidos et al (2023) combined the 4 Gyr M-dwarf gyrochrone of the open cluster M 67 (Dungee et al 2022) with those of younger, previously published gyrochrones 3, 5, and 8). Rotation periods and mass determinations for inactive (white circles) and active (gray circles) stars from Newton et al (2017) are shown for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Empirically calibrated relations between age and period can be used to estimate the ages of individual field stars. Gaidos et al (2023) combined the 4 Gyr M-dwarf gyrochrone of the open cluster M 67 (Dungee et al 2022) with those of younger, previously published gyrochrones 3, 5, and 8). Rotation periods and mass determinations for inactive (white circles) and active (gray circles) stars from Newton et al (2017) are shown for comparison.…”
Section: Discussionmentioning
confidence: 99%